Electrohydrodynamic formation of single and double emulsions for low interfacial tension multiphase systems within microfluidics - Azizian, Pooya; Azarmanesh, Milad; Dejam, Morteza; Mohammadi, Mehdi; Shamsi, Milad; Sanati-Nezhad, Amir; Mohamad, Abdulmajeed A. (Chemical engineering science, 2019)
•Flow parameters effect on the stability of EHD-based droplet formation is investigated.•3D computational analysis of the fluid flow and electrical phenomena is provided.•Effects of capillary number and permittivity ratio on the droplet size are studied.•A new double emulsion formation method based on EHD is suggested. The feasibility of droplet formation from the dispersion of one viscous fluid within another immiscible viscous fluid with low interfacial tension is shown to be very limited. In this work, the process of emulsion formation for low interfacial tension multiphase systems (e.g. aqueous two-phase systems (ATPSs)) was simulated, where the liquids were exposed to an electric field within a microfluidic device. For the first time, the formation of double emulsion via electrohydrodynamic (EHD) force within microfluidics was investigated. A three dimensional (3D) numerical model was developed based on finite-volume discretization of the governing equations to simulate the EHD-based single and double emulsion formation for ATPSs within microfluidics. The dispersed viscous phase moving toward the active electrode is subjected to shear stress, producing instability on the two-phase interface and causing the formation of a necking area. Upon removal of the electric pulse, the dispersed phase moves in the opposite direction resulting in the formation of the droplet. The volume-of-fluid numerical method was applied to trace the two-phase interface, and a height function was imposed to deal with the 3D contact angles. The effect of capillary number and permittivity ratio of the phases on the size and shape of the droplets was assessed and compared with experimental data. Through controlling the interface between the phases, pressure contours, and volumetric charge density contours, it is possible to generate EHD-based single and double emulsions from viscous fluids within microfluidics with applications in drug delivery, tissue engineering and chemical and biological processes.